Factors Affecting the Tourists’ Arrival at Botanical Gardens in Sri Lanka (Peradeniya and Henarathgoda Botanical Gardens) - Gunarathna, Manjula (Department of Social Statistics, Faculty of Social Sciences, University of Kelaniya Sri Lanka, 2022)
Currently, tourism is recognized as an emerging industry worldwide. Due to the wide variety of purposes and preferences that tourists have, the industry has grown exponentially over the years, branching out into different areas among which eco-tourism plays a significant role. In Sri Lanka, the tourism industry plays an undisputable role in the country’s economic growth. However, it can be observed that the contribution of botanical gardens to the development of the Sri Lankan tourism industry has not been acknowledged by the contemporary studies that concern the industry. Therefore, this study aims to identify the prominent factors that influence the change in tourist arrival in both Peradeniya and Henarathgoda botanical gardens. The present study aims to understand the impact of the factors on tourist arrivals to the selected gardens through a sample of 75 local and 25 international tourists, who were selected via an on-site survey. The results of the exploratory factor analysis revealed that gender and age group are the most influential variables that showed different agreement levels in the Peradeniya Botanical Garden, whereas age group, gender, and educational level demonstrated different agreement levels in the Henarathgoda Botanical Garden. The research identified five factors that significantly influenced tourist visits in the Peradeniya botanical garden including external facilities, natural environment, garden environment, transportation and communication, and safety. Similarly, in the Henarathgoda botanical garden, four factors were identified as influential: facilities, transportation, security, parking, sanitation, and natural attraction.
Keywords: Botanic Tourism, Botanical Gardens, Factors, International Tourists, Local Tourists